2014
DOI: 10.1080/10550887.2014.950025
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Drinking Goal and Alcohol Use One Year After Residential Treatment: A Multicenter Study

Abstract: This study examined whether patients' drinking goals at admission to and discharge from 12 residential alcohol use disorder treatment programmes were associated with alcohol-related outcomes at 1-year follow-up. Detoxified patients (N=289) completed assessments at admission, after treatment, and at 1-year follow-up. Drinking goals of abstinence, conditional abstinence (in principle abstinence but potential occurrence of lapses or drinking, when urges are strong), and controlled drinking changed during treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
16
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 21 publications
4
16
1
2
Order By: Relevance
“…Consistent with previous studies (e.g., Adamson et al, 2010;Hodgins, Leigh, Milne, & Gerrish, 1997;Meyer, Wapp, Strik, & Moggi, 2014), clients with at-risk alcohol consumption choosing abstinence showed higher rates of successful treatment outcomes at both follow-up assessments. This difference also remained significant, when controlling for baseline differences between the two goal groups.…”
Section: Discussionsupporting
confidence: 80%
“…Consistent with previous studies (e.g., Adamson et al, 2010;Hodgins, Leigh, Milne, & Gerrish, 1997;Meyer, Wapp, Strik, & Moggi, 2014), clients with at-risk alcohol consumption choosing abstinence showed higher rates of successful treatment outcomes at both follow-up assessments. This difference also remained significant, when controlling for baseline differences between the two goal groups.…”
Section: Discussionsupporting
confidence: 80%
“…On the other hand, several studies have shown that drinking goal preference is a dynamic variable that could change over time in either direction: from abstinence to non-abstinence or vice versa (Enggasser et al, 2015;Hodgins, Leigh, Milne, & Gerrish, 1997;Meyer, Wapp, Strik, & Moggi, 2014;Ojehagen & Berglund, 1989). In a Swiss study involving patients in residential alcohol treatment programs, 46% changed their drinking goal (abstinence, conditional abstinence, or controlled drinking) from treatment admission to discharge (Meyer et al, 2014). The predictive value of drinking goals for drinking outcomes at one-year follow up was notably higher at discharge than admission, with goal abstainers at discharge experiencing the best outcomes.…”
mentioning
confidence: 99%
“…Raittiustavoitteeseen päätyneiden on todettu py syvän raittiina tai ainakin kohtuudessa paremmin kuin muunlaisen tavoitteen valinneet (19)(20)(21)(22). Tässä tutkimuksessa enemmistö tutkittavista valitsi alussa raittiustavoitteen.…”
Section: Pohdintaunclassified
“…Tässä tutkimuksessa enemmistö tutkittavista valitsi alussa raittiustavoitteen. Vaikka vain kol mannes heistä säilytti raittiustavoitteen koko seurannan ajan, niin heillä oli aikaisempien tutki musten (19)(20)(21)(22) tavoin vähemmän runsasta alko holin käyttöä ja enemmän raittiutta kuin vähen tämisen tavoitteekseen valinneilla.. Terveys on tärkeä koettu syy alkoholin käytön lopettamiselle (1)(2)(3)(4)(5)(6). Tässä tutkimuksessa monet riippumatta alun tavoitteesta olivat raittiina useita kuukausia sairastumisen jälkeen ja uudelleen sairastumisen pelko näytti useilla hillitsevän alkoholin käyttöä myös pitkällä aikavälillä.…”
Section: Pohdintaunclassified